Новые таксоны клещей надсемейства Ceratozetoidea (Oribatei) - Павличенко, П.Г. (Вестник зоологии, 1993)
Ceresellidea Pavlitshenko, fam. n. closely related to Ceratozetidae, distinct by the presence of posterior notogastral tectum; included genera: Cyrtozeles B e h a n-P e 1 1 e t i e r, 1985 and Ceresella Pavlitsheko, 1993. Xiphobates Pavlitshenko, gen. n. (type-species: Murcia voigtsi Oudemans, 1902) includes a part of species formerly assigned to Chamobates Hull, 1916, characteristic with large, swordlike, heavily barbed setae on the ventral surface and rectangular free margin of the pteromorph. Ceraiozetella helenae Pavlitshenko, sp. n. is closely related to C. sellnicki (Raj ski, 1958), distinct by dentate tutorium dorsal margin, concave free margin of psdm etc. C. sellnicki (Raj ski, 1958) is redescribed upon type material. Type material of C. helenae sp. n. is deposited in Schmalhausen Institute of Zoology, Ukrainian Academy of Sciences (Kiev).